2015
DOI: 10.1016/j.ijscr.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A case report of duplex gallbladder and review of the literature

Abstract: HighlightsWhat is already known on this topic?Duplex gallbladder is a rare congenital abnormality.What this study adds?The importance of thorough investigation to avoid missed diagnosis.Surgery is only indicated for symptomatic duplex gallbladders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
1
27
0
2
Order By: Relevance
“…Duplication of the gallbladder is a rare congenital anomaly, ever since Blasius et al first decryption in 1675 [ 1 ] few cases have been reported [ 1 , 2 ]. It is estimated that it occurs in every one of 3400 patients [ 2 , 3 ]. This type of anomaly has not predominance over gender, age or ethnical predominance, and is commonly reported during surgical procedures and autopsies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Duplication of the gallbladder is a rare congenital anomaly, ever since Blasius et al first decryption in 1675 [ 1 ] few cases have been reported [ 1 , 2 ]. It is estimated that it occurs in every one of 3400 patients [ 2 , 3 ]. This type of anomaly has not predominance over gender, age or ethnical predominance, and is commonly reported during surgical procedures and autopsies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can appear from two origins, as split primordium or as an accessory gallbladder [ 2 , 3 ]. They can be either asymptomatic, as there are no specific symptoms attributable to a gallbladder duplication [ 4 ], or and can present with symptoms associated with cholelithiasis, cholecystitis, cholangitis or pancreatitis [ 3 , 5 ]. Surgery is the treatment of choice for symptomatic cases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ultrasound imaging can only exclude or document the existance of a double gallbladder but a precise diagnosis needs to differentiate the cystic ducts with their insertion in the biliary tree [ 7 ]. According to Harlaftis suggestion, when MRCP can be performed before surgery [ 8 ] the diagnosis is very useful.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was thereafter confirmed by ultrasound soon after birth although a precise anatomical definition was only obtained by MRCP. To our knowledge, the use of MRCP for this diagnosis has been reported in adults [ 2 , 8 ] but only in one newborn.…”
Section: Discussionmentioning
confidence: 99%